Awareness of HIV/AIDS among Selected Secondary School Students in Kaduna Metropolis, Kaduna State - N. Idris, Idoko, (Kashere Journal of Education, 2021)
This study assesses the awareness of HIV/AIDS among selected Secondary School Students in Kaduna Metropolis, Kaduna State. The study used survey research design with a sample of 400 students selected from four secondary schools in Kaduna Metropolis using multi-stage sampling procedure. A questionnaire was used as an instrument for data collection. The instrument was validated by experts and subjected to reliability check. The data was analysed using mean scores and standard deviations in answering the research questions whereby a cut-off point of 3.00 and above was taken as positive response and accepted while less than 3.00 was considered a negative response and rejected. The study concluded that secondary school students were aware and has knowledge on HIV/AIDS in Kaduna Metropolis. However, chances of knowing more are affected by language used, terminologies, no feedback channel of communication and inadequate sex education. The study recommends among others that secondary schools in Kaduna Metropolis in particular and Kaduna State in general should increase the level of awareness of HIV/AIDS and other sexual education among secondary school students to aid them makes inform decision about their sexuality.